Comparison of the high-temperature corrosion of aluminium nitride, alumina, magnesia and zirconia ceramics by coal ashes. Issue 7 (August 2015) - Himpel, Gert; Herrmann, Mathias; Höhn, Sören
Abstract: Higher-grade reactor lining materials are needed to withstand the higher working temperatures and gas pressures used in gasification reactors to improve their efficiency. Both conventional oxide materials and nonoxide materials such as SiC and AlN are suitable refractory materials for the reducing atmospheres prevailing in gasifiers. Interactions between the reactor lining and the slag constitute the main corrosion mechanism. In previous investigations on the high-temperature corrosion of aluminium nitride by coal ash[1] AlN materials were tested in basic and acidic coal ashes at temperatures of 900–1300 °C. In the present work the high-temperature corrosion of aluminium nitride by different coal ashes is compared with that of alumina, magnesia and zirconia.